Determinan penggunaan kelambu berinsektisida di Bengkulu: analisis riskesdas - Lina Apriana; Riris Andono Ahmad; Yodi Mahendradhata (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Determinant factors affecting the use of insecticide-treated nets in Bengkulu: analysis from basic health survey 2013PurposeThis study aimed to identify determinant factors that influence the use of insecticide-treated nets and to evaluate the effectivity of the mosquito nets usage, in pregnant women and young children in Bengkulu, based on basic health survey 2013.MethodThis study used a cross-sectional design. Study population were all members of households in Bengkulu that used insecticide-treated nets, based on basic health survey 2013.ResultsThere were no significant correlations between employment status, education, vulnerable children, use of community health center, housing, and use of wire gauze with insecticide-treated nets. Multivariate logistic regression tests showed that there were some socio-demographic variables, behavior, and environment that affected mosquito net usage.ConclusionSocial determinants of demographic factors, behavioral determinant factors, environmental determinant factors, and presence of children affected the use of insecticide-treated nets, but the use of mosquito nets was not effective against vulnerable groups (pregnant women).